Gem-diol Generation in Copper and Zinc N-methyl-2-imidazolecarboxaldehyde Complexes: Solid-state NMR, EPR and Single-Crystal X-ray Studies - Crespi, Ayelen Florencia (2023)
Novel coordination compounds, mono- (1) and binuclear copper complexes (2) and a zinc complex (3) were synthesized and studied through single-crystal X-ray crystallography, solid-state NMR and EPR techniques to determine the chemical functionalization of the carbonyl group in N-methyl-2-imidazolecarboxaldehyde ligand. Particularly, molecules containing carbonyl groups are versatile ligands that give rise to a wide range of new materials due to the high reactivity of the carbonyl group. However, the chemical identification of the functional group present in these coordination compounds is a challenge because the copper ion affects the NMR signals. In this sense, X-ray crystallography becomes an indispensable tool for the analysis. The imidazole ligands in copper complexes 1 and 2 were found to be the aldehyde and the gem-diol forms, respectively. Furthermore, the gem-diol and carboxylate moieties were detected in the crystal lattice for the zinc complex 3 and studied by solution- and solid-state NMR.